Higher Education Policy Implementation and Academic Performance: The Mediating Role of Job Satisfaction Among Lecturers in Indonesian Maritime Institutions - Mudakir Mudakir; Eleonora Sofilda; Syofriza Syofyan (Universitas Muhammadiyah Mataram, 2026)
Higher education policy implementation in maritime institutions under Ministry of Transportation governance critically influences lecturer performance and job satisfaction. This convergent parallel mixed-methods research employing SEM-PLS quantitative analysis and systematic literature review examined competence, compensation, career development, leadership style, organizational culture, digitalization, and institutional policy effects on outcomes across 425 lecturers from fourteen Indonesian maritime institutions. Quantitative findings reveal digitalization quality (β=0.412, p<0.001), institutional policy clarity (β=0.387, p<0.001), and lecturer competence (β=0.356, p<0.001) exert strong significant effects on job satisfaction and performance, while organizational culture, leadership style, compensation, and career development demonstrate non-significant relationships constrained by bureaucratic governance mechanisms. Job satisfaction mediates 31.9% of institutional factors' performance effects (indirect β=0.187, p<0.001), with reciprocal smaller performance mediation on satisfaction (indirect β=0.094, p=0.001). Systematic literature review of 347 articles validates digitalization, policy, and competence importance while revealing compensation, career, leadership, and culture effects depend on governance flexibility absent in transportation ministry contexts. Research recommends prioritizing digitalization enhancement, policy clarification, and competence development within current constraints while advocating governance reforms enabling compensation flexibility, career structure revision, leadership transformation, and culture evolution.